Implementation of Mixed-Election System as a Way to Purify Indonesian Presidential System: Penerapan Sistem Pemilu Campuran Sebagai Upaya Purifikasi Sistem Presidensial di Indonesia - Eugen Mohamad (Jurnal Konstitusi, 2025)
The presidential system in Indonesia faces challenges because it operates alongside an extreme multiparty system. Previous research has shown a mismatch, as the president and his administration experience deadlock and immobilism. Party simplification is one step toward purifying the presidential system and can be pursued through electoral-system engineering. This study employs a normative legal research method. It aims to design a mixed electoral system for Indonesia, assess its compatibility, and simulate its effects. The findings indicate that, in post-reform Indonesia, the use of a proportional-representation system has produced extreme multiparty practices. Implementing a mixed electoral system is an alternative worth considering to purify the presidential system. This aligns with Constitutional Court Decision No. 114/PUU-XX/2022, which, in its legal considerations, calls for improvements to the proportional system, even while rejecting a closed-list proportional electoral system in its ruling. Based on simulations applying a mixed electoral system to the 2009, 2014, 2019, and 2024 elections, a minimum majority party is produced in parliament. To implement this system, it is necessary to revise the Election Law, especially Article 168.